Pemanfaatan Youtube dalam Menanamkan Tata Cara Ibadah Pada Santri Pondok Pesantren - Rahmat, Ilham; Nasution, Muhammad Irwan Padli; Nasution, Wahyudin Nur (Innovative: Journal Of Social Science Research, 2025)
This study aims to examine the use of the YouTube platform as a learning medium in instilling worship procedures to students in Islamic boarding schools. Using a descriptive qualitative approach, this study was conducted on male and female students at the Al-Uswah Kuala Islamic Boarding School, Langkat Regency. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study indicate that YouTube is able to be an effective visualization media in bridging the theory and practice of worship, especially for students with visual and kinesthetic learning styles. The main advantages of YouTube lie in the flexibility of learning time, accessibility of materials, and the ability to repeat videos that support personalization of learning. In addition, this media increases the motivation and involvement of students in the learning process, and encourages the implementation of a blended learning model that combines traditional Islamic boarding school methods with digital technology. However, there are challenges such as limited infrastructure, digital literacy, and the risk of content that is not in accordance with Islamic values. The proposed solutions include content curation, digital literacy development, and development of Islamic boarding school media facilities. Overall, YouTube has been proven to make a significant contribution to improving the quality of students' understanding and practice of worship contextually and adaptively to the development of the times.